The existence of Asian small-clawed otter (Aonyx cinereus Illiger, 1815) in the UCPS Hydropower, Cianjur, West Java, Indonesia - Abdiel Praha Dirgantara; Erri Noviar Megantara; Teguh Husodo; Puput Febrianto; Indri Wulandari; Sya Sya Shanida (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Dirgantara AP, Megantara EN, Husodo T, Febrianto P, Wulandari I, Shanida SS. 2021. The existence of Asian small-clawed otter (Aonyx cinereus Illiger, 1815) in the UCPS Hydropower, Cianjur, West Java. Biodiversitas 22: 4391-4401. Little information about the existence of small-clawed otters (Aonyx cinereus) in Indonesia is available. Small-clawed otter is the top predator and biological indicator of wetland health. However, the small-clawed otter population in the world has decreased due to anthropogenic factors. This study aims to reveal 1) estimate the population size of small-clawed otters and 2) the small-clawed otter signs at the UCPS Hydropower construction site, Cianjur, West Java. This study used a qualitative approach in February-April 2017. Sign surveys (feces, footprints, leftovers, and dens) and camera trapping were applied in this study. There were 32 signs with details of 21 feces, eight footprints, and three dens. The estimation of small-clawed otter population size at UCPS Hydropower ranges from 5-14 individuals in total scattered in the Citali-Cisokan, Cilengkong, and Cirumamis rivers. In addition, the discovery of infant and bedding repair activities shows that the habitat in the UCPS Hydropower area supports the daily needs of small-clawed otters, especially in terms of breeding and shelter. Further studies are needed regarding the impact of the UCPS Hydropower construction on the existence of small-clawed otters, especially in the overlapping between small-clawed otter habitat and the UCPS Hydropower construction sites, by monitoring and making wildlife management policies.